Diagnosis and Management of Constipation : A Narrative Literature Review - Ridwan, Muhammad (Phlox Institute: Indonesian Medical Research Organization, 2023)
Constipation can occur as a primary or secondary condition. This literature review aimed to describe the diagnosis and management of constipation. Primary constipation is generally classified into three categories. Normal transit (functional) constipation involves a normal rate of passage of stool, but there is difficulty wit h the evacuation of the stool. Functional constipation is most common and is associated with a sedentary lifestyle, a low-residue diet (consumption of very refined foods), or low fluid intake, which decreases stool volume and bulk and can lead to constipation. Lack of access to toilet facilities, consistent su ppression of the urge to empty the bowels, and dehydration are other causes. Slow transit constipation involves impaired motor activity of the colon with infrequent bowel movements, straining to have a bowel movement, mild abdomi nal distention, and palpable stool in the sigmoid colon. Pelvic floor dysfunction (pelvic floor dyssynergia-anismus), or outlet dysfunction, is difficulty pas sing stool due to failure of the pelvic floor muscles or anal sphincter to relax with a bowel movement.